Consequences of job embeddedness and the mediating role of continuance commitment on intention to stay in Malaysian Information and Communication Technology Industry - Ayesha, Noor (2020)
Investigating employee’s intention to stay is particularly important within the Malaysian Information and Communication Technology sector, which is characterized by high turnover and the impact of the global shortage of skilled employee’s. The managers need to recognize the value of their employee’s by encouraging them to remain for their resource talent to be used, and also discourage them from looking elsewhere for better opportunities. Grounded in Job Embeddedness and Social Exchange theory, the purpose of this study was to investigate the relationship between job embeddedness (on-the-job and off-the-job) and intention to stay with the mediating relationship of continuance commitment. Additionally, these relationships further enhance and evaluate the extent to which job embeddedness (on-the-job and off-the-job) influences employee’s intention to stay. A survey was conducted with total of 177 personally administrative structured questionnaires were obtained with the response rate of 70.8%. SPSS 20.0 & SmartPLS 3 for structural equation modeling was utilized in confirming the hypotheses developed for the study. The results of the structural equation modeling analysis indicated the model was substantial. The findings of the study also revealed that there was a significant positive relation between fit and links dimension of on-the-job; off-the job embeddedness and intention to stay. At the same time, continuance commitment partially mediates these relationships. Moreover, continuance commitment plays full mediation between sacrifice organization and intention to stay. The results not only supported previous outcomes that people who were more embedded in their jobs had more intent to stay, but also expanded the significance of off-the-job and non- affective reasons of staying job. This research adds to the body of knowledge concerning what contributes to why people stay their jobs. Reduced employee turnover can financially benefit to Malaysian Information and Communication Technology Industry organization and that in turn can have a positive social benefit on the community.